Changes in the abundance and distribution of rorqual prey in the Northeast United States over four decades - Julia E. F. Stepanuk; Janet A. Nye; Nicholas R. Record; Lesley H. Thorne (Ecosphere)
Abstract The distribution, phenology, and population dynamics of species at multiple trophic levels have been impacted by climate change across a range of spatial scales. Upper trophic level species may be uniquely impacted through changes to prey species and foraging habitats in space and time. Improving our understanding of how known changes in the abundance and distribution of prey species influence prey availability for marine predators is key to understanding climate impacts on upper trophic level species. Rorquals, a group of baleen whales, are generalist feeders that employ lunge feeding to engulf large volumes of water and prey, thereby requiring dense aggregations of prey for efficient feeding. While climate‐driven changes have been well documented for some species of fish and invertebrates consumed by rorquals, changes to the distribution of rorqual prey in aggregate and the implications of these changes for rorqual foraging habitat have received little attention. We used a 40‐year time series of prey data to assess spatial and temporal shifts in key prey groups for four rorqual species in the rapidly warming Northeast United States. We found notable changes to the distribution and biomass of prey groups for rorquals through space and time. The center of biomass of key large‐bodied prey showed significant poleward shifts and biomass increased in the northern portion of the Northeast United States. Accordingly, we found significant increases in the biomass of large‐bodied humpback, minke, and fin whale prey in the northerly Gulf of Maine and George's Bank regions, with concurrent decreases in the biomass of large‐bodied humpback whale prey in more southernly Mid‐Atlantic Bight and Southern New England regions. In contrast, there was little evidence of change in the distribution and biomass of smaller prey groups, which are of key importance for sei and fin whales. Our results suggest that rorquals that primarily consume large‐bodied prey, humpback and minke whales, may be more likely to be impacted by climate‐driven shifts in prey than sei and fin whales that feed on smaller prey. Assessments of changing prey distributions are needed for proactive management in light of climate‐driven impacts on whale foraging habitat.